Influence of maximal strength on in-water and dry-land performance in young water polo players - Keiner, M.; Rähse, H.; Wirth, K.; Hartmann, H.; Fries, K.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2020)
Water polo is a multifaceted sport that is characterized by explosive actions, including sprint swimming, jumping, throwing, and struggling against opponents. Based on these factors, maximal and speed strength may be important characteristics to develop in-water polo players. However, more research is needed to further understand the relationship between various strength characteristics and water polo performance. Therefore, the primary purpose of this study was to examine the relationships between strength, speed strength, and markers of water polo performance in youth water polo players. Sixty-one male youth water polo players (10-14 years, 11.9 ± 1.3 years) had their 1-repetition maximum (1RM) bench press and squat, dry-land speed-strength performance (squat jump [SJ], countermovement jump [CMJ], and medicine ball throw), in-water performance (sprint swim and water jump), and anthropometric measurements assessed. Fifty to 60% of the variance in sprint performance was explained by the 1RM bench press and arm span. The influence of the bench press 1RM was more than twice that of the anthropometric factors. Maximum strength in the squat and speed-strength (jump height in SJ, CMJ) variables explained 18-25% variance in the eggbeater kick (a leg strike technique to stay above and jump out of water), and the bench press 1RM explained the 42% of the variance in loaded throws without the influence of anthropometric factors. This study suggests that upper- and lower-body maximal strength parameters are important predictors of the performance capacity of water polo players.